1997
DOI: 10.1212/wnl.49.4.1131
|View full text |Cite
|
Sign up to set email alerts
|

CSF antigliadin antibodies and the Ramsay Hunt syndrome

Abstract: Although the association between celiac disease and progressive myoclonic ataxia is well recognized, in each of the reported cases the neurologic features began in middle adult life and usually in patients who had clinical or laboratory evidence of malabsorption. We report a case of progressive myoclonic ataxia and epilepsy (Ramsay Hunt syndrome) that began in childhood. In this patient there were no features suggestive of gluten intolerance. The presence of antigliadin antibodies in the serum and CSF suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 5 publications
1
21
0
1
Order By: Relevance
“…The association between myoclonic ataxia and celiac disease in adult life is confirmed by Chinnery et al 18 who recorded the history of a girl who at the age of 8 years started to have myoclonus followed by absence seizures and one generalised seizure. Her development was delayed and she became increasingly ataxic during adolescence.…”
Section: Cerebellar Ataxiamentioning
confidence: 74%
See 1 more Smart Citation
“…The association between myoclonic ataxia and celiac disease in adult life is confirmed by Chinnery et al 18 who recorded the history of a girl who at the age of 8 years started to have myoclonus followed by absence seizures and one generalised seizure. Her development was delayed and she became increasingly ataxic during adolescence.…”
Section: Cerebellar Ataxiamentioning
confidence: 74%
“…The presence of antigliadin antibodies in the serum, although a non-specific finding, may suggest the diagnosis of celiac disease, and if found in the CSF, even more so 18 . The high prevalence of circulating antigliadin antibodies, IgG, IgA, or both, in patients with obscure neurological disorders was 57% compared with 5% in those with specific neurological diseases and 12% in healthy control individuals.…”
Section: Diagnosismentioning
confidence: 99%
“…AGA has been found in the CSF of one patient with myoclonic ataxia and gluten sensitive enteropathy but this may have represented leakage from the serum via a disrupted blood-brain barrier. 27 In the few ataxic patients with CD that have come to postmortem Purkinje cell loss and astrocytosis seem to be prominent features but Hadjivassilou et al also demonstrated lymphocytic infiltrates in two of their patients at necropsy, suggesting immune mediated damage. 13 Pellechia et al reported a single case of "gluten ataxia" where symptoms responded to gluten restriction.…”
Section: Discussionmentioning
confidence: 98%
“…Antigliadin antibodies have been found in the cerebrospinal fluid in patients with gluten sensitivity and neurological dysfunction 23 . Nevertheless, these antibodies are present in almost all patients with CD, but only a small proportion of them develop neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%